2015
DOI: 10.3390/w7031217
|View full text |Cite
|
Sign up to set email alerts
|

Home Water Treatment Habits and Effectiveness in a Rural Arizona Community

Abstract: Drinking water quality in the United States (US) is among the safest in the world. However, many residents, often in rural areas, rely on unregulated private wells or small municipal utilities for water needs. These utilities may violate the Safe Drinking Water Act contaminant guidelines, often because they lack the required financial resources. Residents may use alternative water sources or install a home water treatment system. Despite increased home water treatment adoption, few studies have examined their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
1
29
1
Order By: Relevance
“…8 In the current study we found crude rates of testing were lowest among younger individuals and those with lower education and lower income. Income was also a predictor of treatment in this study, and education an important predictor of treatment in other studies 10, 19, 37 providing further evidence that lower SES individuals are likely most vulnerable based on both greater potential for exposure and differences in well stewardship. 28 Given the strong association between treatment rates and higher income, the costs of treatment may be a barrier to both testing and treatment.…”
Section: Discussionsupporting
confidence: 73%
“…8 In the current study we found crude rates of testing were lowest among younger individuals and those with lower education and lower income. Income was also a predictor of treatment in this study, and education an important predictor of treatment in other studies 10, 19, 37 providing further evidence that lower SES individuals are likely most vulnerable based on both greater potential for exposure and differences in well stewardship. 28 Given the strong association between treatment rates and higher income, the costs of treatment may be a barrier to both testing and treatment.…”
Section: Discussionsupporting
confidence: 73%
“…If considering only treatment methods that are capable of removing arsenic from the water, then the rates of use are 17% and 9%, respectively. A recent study of private well owners in Arizona similarly found that household income and education were significant predictors of water treatment (Lothrop et al, 2015). For arsenic specifically we have previously found that while taking any mitigation action was not associated with SES, choice of mitigation action is significantly associated with income and education.…”
Section: Discussionmentioning
confidence: 99%
“…In our water sampling in New Jersey (18% of n=22) and in Maine (15% of n=68) we have identified multiple examples of incorrect or ineffective treatment systems failing to deliver water below the arsenic MCL arsenic at the tap, 28,30 and similarly ineffective treatment has been observed elsewhere by others. 32,33 Several NJ well owners who sent water samples believed they were treating for arsenic because there was a system in their basement, although they did not know what kind of system it was and had never performed any maintenance on it. The presence of tanks in the basement can give the false assurance of safe water leaving well owners unconcerned about monitoring the quality of their water.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of households living with arsenic in their well water show that due to deficiencies in technology and behavior in practice, real elimination of arsenic exposure is elusive. 30,32,34 Once significant gains in arsenic screening are achieved, shifting resources to education and support for these households facing arsenic problems in their well water will be necessary.…”
Section: Discussionmentioning
confidence: 99%